THE USE OF RICE HULL FERMENTED IN DIETS SUPPLEMENTED PURPLE SWEET POTATO(IPOMOEA BATATAS L.) LEAVES MEAL ON PERFORMANCE OF 36 WEEKS OF AGE BALI DUCKS - SUSILA T. G. O.; T. G. B. YADNYA; A. A. A. S. TRISNADEWI (Majalah Ilmiah Peternakan, 2018)
The experiment was carried out to study the effect on fermented rice hull in diets supplemented with purplesweet potato (Ipomoea batatas L.) leaves meal on performance of bali ducks. A completely randomized design withfive treatments such as diet without rice hull (A), diet contaning 10% rice hull (B), diet containing 10% fermentedrice hull (C), ration contaning 9% rice hull and 1% purple sweet potato leaf meal (D), diet containing 9% fermentedrice hull and 1% purple sweet potato leaf meal (E). Each treatment in three replications consists of 5 female ducks.The variables observed were feed consumption, antioxidant capacity, total egg weight and FCR, and total eggs, eggproduction per day, and means of eggs weight. It showed that diet feed consumption of ducks fed E treatment found3.32% lower (P<0,05), total eggs 47,56% higher (P<0,05) compared to A. In addition, E treatment can increasetotal amount of eggs, egg production per day, and 29,16%, 29,15% dan 12,12% means of eggs (P<0,05) compared toA treatment. It can be concluded that ducks fed diets containing fermented rice hull and purple sweet potato leafmeal supplemented can improve efficiency of diets and production of eggs.